Riziko vzniku kolorektálního karcinomu u nemocných s ulcerózní kolitidou - Jablonská, M; Rezníková, L; Pesková, M; Chlumská, A; Roth, J (Vnitrni lekarstvi, 1993)
In patients with ulcerative colitis of prolonged duration and major extent there is according to the majority of investigations an increased risk of development of colorectal carcinoma; the magnitude of the risk which is of major importance for clinical practice, however, differs according to different authors. The present study comprises 189 patients with ulcerative colitis, 103 men and 86 women, perspectively followed up for a period of 12.5 years (8.0-24.5). In 60 patients the distal form was present, in 68 left-sided colitis and in 61 pancolitis. The patients were monitored systematically--clinically colonoscopically and endoscopically. The intervals between these check-ups were gradually shorter when the disease persisted for 10 or 12 years, i.e. the patients were checked once to twice a year. The endoscopic findings were focused in particular on evidence of dysplasia. The follow-up system was modified with regard to individual conditions. In the course of the follow-up colorectal carcinoma was detected in 9 patients (4.8%) with a persistence of the disease for 9-25 years (in one patient after 9 years, in 5 after 10-20 years and in 3 after longer periods). In three instances the left-sided form was involved, in 6 pancolitis. Dysplastic changes were mostly medium grade and were found at least once in all patients. The preoperative diagnosis of carcinoma was established for certain in three patients, there was major suspicion in four patients. In two patients the carcinoma was detected only on operation (in active forms of the disease). All carcinomas were resectable, 4 times DUKES A, 4 times B, once C. As to the remaining 180 patients, 32 were operated on account of colitis; in 28 at least once dysplasia was proved, with a rising trend as the disease had a prolonged duration. These results confirm the increased risk of carcinoma in ulcerative colitis with a long duration and with a major extent and justify systematic colonoscopic and endobioptic follow-up of these patients.
Keywords: Male; lidé středního věku; ulcerózní kolitida; Humans; Colitis, Ulcerative; Middle Aged; senioři; rizikové faktory; kolorektální nádory; mužské pohlaví; Female; mladiství; Aged; ženské pohlaví; Colorectal Neoplasms; Adult; Adolescent; dospělí; lidé; Risk Factors